Strategi Komunikasi Pemasaran Program Interaktif di Media Radio - Farid Rusdi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2011)
Most of radio stations today is involving the audiences through the interactive program. This changes is related with the reformation order, particularly in developing public sphere, meaning that society is more open than before. Some of the radio stations create this interactive program as their main positioning. In the competition among the radio station, marketing communication strategy is needed. This article discuss about how the station radio using the marketing communication strategy to win the competition.